2020
DOI: 10.3390/met10091162
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Angular Co-Extrusion: Geometrical and Mechanical Properties of Compound Profiles

Abstract: A novel co-extrusion process for the production of coaxially reinforced hollow profiles has been developed. Using this process, hybrid hollow profiles made of the aluminum alloy EN AW-6082 and the case-hardening steel 20MnCr5 (AISI 5120) were produced, which can be forged into hybrid bearing bushings by subsequent die forging. For the purpose of co-extrusion, a modular tooling concept was developed where steel tubes made of 20MnCr5 are fed laterally into the tool. This LACE (lateral angular co-extrusion) proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 15 publications
1
26
0
Order By: Relevance
“…The workpieces were fabricated by machining, fitted together with a tolerance H7/g6 for a diameter of 44 mm (clearance fit) without metallurgical bonding, and subsequently formed to the final geometry. The steel thickness investigated in this work was chosen by analogy with the coextrusion process, which produces hybrid workpieces with initial bonds for further investigation, in order to be able to make a comparison [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…The workpieces were fabricated by machining, fitted together with a tolerance H7/g6 for a diameter of 44 mm (clearance fit) without metallurgical bonding, and subsequently formed to the final geometry. The steel thickness investigated in this work was chosen by analogy with the coextrusion process, which produces hybrid workpieces with initial bonds for further investigation, in order to be able to make a comparison [ 20 ].…”
Section: Methodsmentioning
confidence: 99%
“…• Conventional billets: This variant is based on the use of mono-material billets without reinforcement, as these are Fig. 1 Schematic Tailored Forming process chain for the demonstrator component of the hybrid bearing bushing, starting with a Lateral Angular Co-Extrusion (LACE) process for the manufacture of the bi-metal semi-finished products and subsequent forming into the aluminum/steel bulk metal component by die forging; according to [5] commonly used in industrial extrusion approaches. The reinforcing element is thus, introduced into the forming zone from the outside and, unlike the matrix material, not deformed plastically [11].…”
Section: Manufacturing Of Hybrid Workpieces By Co-extrusionmentioning
confidence: 99%
“…Recent investigations by Thürer et al employing a new tool design at near-industrial scale as well as 20MnCr5 steel tubes as reinforcing elements have already shown that sufficiently coaxial aluminum-steel hollow profiles featuring reinforcement contents of both 14 vol% and 34 vol% can be successfully achieved. In addition, shear strengths of up to 58 MPa ± 15 MPa were determined on sample segments that included the joining zone, which indicated the presence of a metallurgical bond by adhesion of aluminum to the steel [5]. For the planned subsequent die forging step within the Tailored Forming process chain (compare schematic process chain in Fig.…”
Section: Manufacturing Of Hybrid Workpieces By Co-extrusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The required materials are joined to hollow steel-aluminium profiles by a co-extrusion process. After the joining, there is a metallurgical bond without intermetallic phase in the interface zone [23]. The presented work considers a strategy for setting the required temperature gradient in the above-described workpieces before the forging process.…”
Section: Bearing Bushingmentioning
confidence: 99%